2019
DOI: 10.3390/antiox8110513
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Reactive Oxygen Species in Health and Disease

Abstract: In diverse living organisms, signaling within the cell, chemical communication between cells or simply the fate of cells to survive or die is largely dependent on the intricate balance of control mechanisms related to reactive oxygen species (ROS)[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Transition metals such as Zn, which were counted at a relatively low weight ratio in the samples, but were detected at constant levels in all samples, can generate ROS in living organisms. ROS are involved in the complex balance of control mechanisms that contribute to cell survival or death through intracellular signal transduction and chem- ical communication between cells (Habtemariam, 2019).…”
Section: Carbon Compound Particle Analysismentioning
confidence: 99%
“…Transition metals such as Zn, which were counted at a relatively low weight ratio in the samples, but were detected at constant levels in all samples, can generate ROS in living organisms. ROS are involved in the complex balance of control mechanisms that contribute to cell survival or death through intracellular signal transduction and chem- ical communication between cells (Habtemariam, 2019).…”
Section: Carbon Compound Particle Analysismentioning
confidence: 99%
“…Some of these ROS are produced during normal cellular metabolism and they have an endogenous origin, mainly by Complex I and III, but there are ROS engendered due to the influence of external factors such as radiation, UV radiation, and heavy metals [33,34]. Although normal ROS production levels play an important role in maintaining proper intracellular signaling, increased levels of ROS production or dysfunction of the cell's antioxidant defense mechanisms may be the initial trigger factor for a wide range of diseases [35,36]. Functional abnormalities in complex I, which are a consequence of gene mutations (nuclear or mtDNA), lead to increased ROS production and a decrease of the energetic cellular capacity [32,37].…”
Section: Disease-associated Defects In Oxidative Phosphorylationmentioning
confidence: 99%
“…In particular, the oxidized functional groups generated due to degradation make the polymer surface hydrophilic, and simultaneously cause coordination bonds with metals. Additionally, Krehula et al demonstrated that polyethylene could be decomposed under outdoor climate conditions to form carbonyl and vinyl groups, as shown in Figure 9a [69]. Therefore, as shown in Figure 9b,c, degradation of LDPE occurs, which may promote interaction between metal components and LDPE (coordination bonding and electrostatic attraction, etc.)…”
Section: R Review 11 Of 18mentioning
confidence: 99%